2023
DOI: 10.1097/qad.0000000000003577
|View full text |Cite
|
Sign up to set email alerts
|

No association between use of tenofovir disoproxil fumarate, etravirine, or integrase-strand transfer inhibitors and acquisition or severe outcomes of SARS-CoV-2 infection in people with HIV in the Netherlands

Abstract: In two Dutch observational cohorts of people with HIV, the use of TDF, ETR, or INSTIs was not independently associated with either the risk of incident SARS-CoV-2 infection or severe COVID-19 outcomes, as was suggested by previous observational and molecular docking studies. Our findings do not support a strategy of modifying antiretroviral therapy to include these agents to protect against SARS-CoV-2 infection and severe COVID-19 outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There have been a number of reports that TFV, a component of the ART regimen given to our study participants and possibly antiretrovirals inhibit SARS-CoV-2 infection [78][79][80] . Other studies did not observe an association between ART and SARS-CoV-2 clearance 81,82 . To investigate whether the TLD ART regimen used in the study could inhibit SARS-CoV-2, we tested the effect of TFV/3TC/ DTG co-formulated ART on SARS-CoV-2 and HIV infection in vitro (Supplementary Fig.…”
Section: Clearance Of Prolonged Sars-cov-2 Infection Associates With ...mentioning
confidence: 83%
“…There have been a number of reports that TFV, a component of the ART regimen given to our study participants and possibly antiretrovirals inhibit SARS-CoV-2 infection [78][79][80] . Other studies did not observe an association between ART and SARS-CoV-2 clearance 81,82 . To investigate whether the TLD ART regimen used in the study could inhibit SARS-CoV-2, we tested the effect of TFV/3TC/ DTG co-formulated ART on SARS-CoV-2 and HIV infection in vitro (Supplementary Fig.…”
Section: Clearance Of Prolonged Sars-cov-2 Infection Associates With ...mentioning
confidence: 83%
“…However, a well designed study published in the current issue of the AIDS by Verburgh et al . [1] found no association between antiretroviral drugs and the acquisition or severe evolution of SARS-CoV-2 disease in HIV-infected people.…”
mentioning
confidence: 75%
“…However, other studies have not confirmed these findings [16]. Furthermore, some studies, such as that by Verburgh et al [1], have ruled out any association between other antiretroviral drugs, such as etravirine (ETR) or integrase strand transfer inhibitors (INSTIs), and the acquisition or serious outcomes of SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…In keeping with evidence-based medical practice, patients with COVID-19 must be treated with efficacious medications; they deserve nothing less”. Similarly, an editorial by Dr. Abrescia, concerning a study which showed a lack of association between antiretroviral use and the acquisition or severe outcomes of SARS-CoV-2 infection in people with HIV in the Netherlands, recommended the following: “If SARS-CoV-2 infection does take place, drugs proven to be effective against SARS-CoV-2 (remdesivir or nirmatrelvir/ritonavir) should be started within five days of the onset of symptoms” [ 207 , 208 ]. Our calculations of the unbound C max /EC 50 ratios and EC 50 measurements in the cell systems relevant to in vivo SARS-CoV-2 infection lends further support to that conclusion.…”
Section: Discussionmentioning
confidence: 99%